2021
DOI: 10.34172/jcvtr.2021.32
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific characteristics of hypertrophic response in cardiomyocytes derived from human embryonic stem cells

Abstract: Introduction: Gender-specific phenotypes of the heart were reported with respect to both physiology and pathology. While most differences were associated with the sex hormones, differential expression of genes received special attention, particularly X-Y chromosomes’ genes. Methods: Here, we compared cardiogenesis by gene expression analysis of lineage specific markers and X-Y chromosomes’ genes, during in vitro differentiation of XY and XX human embryonic stem cells (hESC), in a hormone-free setup. Results: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Among them, one study looked at sex differences in hESC-CM hypertrophy in response to isoproterenol using one female and one male line. Results showed that female CM undergo hypertrophy more slowly in response to isoproterenol indicating cellular level differences in CM hypertrophy without the addition of hormones 28 . In another study, three female and three male hiPSC-CM lines from different ethnic origins were tested for sensitivity to various pharmacological agents 29 .…”
Section: Introductionmentioning
confidence: 95%
“…Among them, one study looked at sex differences in hESC-CM hypertrophy in response to isoproterenol using one female and one male line. Results showed that female CM undergo hypertrophy more slowly in response to isoproterenol indicating cellular level differences in CM hypertrophy without the addition of hormones 28 . In another study, three female and three male hiPSC-CM lines from different ethnic origins were tested for sensitivity to various pharmacological agents 29 .…”
Section: Introductionmentioning
confidence: 95%